The Effect of Market Orientation, Learning Orientation, and Entrepreneurial Orientation on Marketing Performance with Competitive Advantage as an Intervening Variable - Evan Haviana; Fajriani Azis (Universitas Negeri Makassar, 2024)
This study aims to determine the direct and indirect influences of market orientation, learning orientation, and entrepreneurial orientation on marketing performance through competitive advantages in active students of the Makassar State University entrepreneurship study program. The research method used in this study is quantitative. The population in this study is all Makassar State University students for the 2023/2024 academic year with a total sample of 50 students. Based on the results of the research that has been done, this research can be a source of information or reference for teaching staff or lecturers in order to be able to direct and guide students related to the development of one's behavior in entrepreneurial desires, students are expected to be able to further deepen their knowledge related to some of the importance of marketing performance so that it is not focused on scientific theory that produced only, but also able to conduct business ventures and develop them in accordance with existing practices. For further research, efforts will be made to deepen and expand this research both in terms of variables and the development of research methods.